2021
DOI: 10.1111/ajt.16567
|View full text |Cite
|
Sign up to set email alerts
|

Remote intervention engagement and outcomes in the Clinical Trials in Organ Transplantation in Children consortium multisite trial

Abstract: Remote interventions are increasingly used in transplant medicine but have rarely been rigorously evaluated. We investigated a remote intervention targeting immunosuppressant management in pediatric lung transplant recipients. Patients were recruited from a larger multisite trial if they had a Medication Level Variability Index (MLVI) ≥2.0, indicating worrisome tacrolimus level fluctuation. The manualized intervention included three weekly phone calls and regular follow-up calls. A comparison group included pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Integrated preventative behavioral health care is critical for pediatric SOT patients during the 3-year posttransplant period to prevent nonadherence and subsequent graft loss and/or mortality, and to address common emotional and behavioral issues that contribute to these medical concerns (Connelly et al, 2015; Duncan-Park et al, 2021; Killian et al, 2018; Reed-Knight et al, 2013; Shaw et al, 2003; Simons & Blount, 2007). In response to a growing patient population at this medical center and recognition of adherence challenges that may impact graft outcomes, the SOT psychology team implemented a targeted, preventative care model of psychology service delivery that included a standardized and more frequent schedule of integrated health and behavior assessments and interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Integrated preventative behavioral health care is critical for pediatric SOT patients during the 3-year posttransplant period to prevent nonadherence and subsequent graft loss and/or mortality, and to address common emotional and behavioral issues that contribute to these medical concerns (Connelly et al, 2015; Duncan-Park et al, 2021; Killian et al, 2018; Reed-Knight et al, 2013; Shaw et al, 2003; Simons & Blount, 2007). In response to a growing patient population at this medical center and recognition of adherence challenges that may impact graft outcomes, the SOT psychology team implemented a targeted, preventative care model of psychology service delivery that included a standardized and more frequent schedule of integrated health and behavior assessments and interventions.…”
Section: Discussionmentioning
confidence: 99%
“…NCT01960322, NCT02320422, NCT02266888). [38][39][40][41][42] Thirteen interventionists have been or are currently involved with the study. Interventionists are located offsite on the east and west coasts of the United States and have not met participants in person.…”
Section: Intervention Designmentioning
confidence: 99%
“…Moreover, it has been reported that the COVID-19 epidemic and the related logistical problems have increased the rejection rates [ 72 ]. One recent trial including paediatric lung transplant recipients found a reduction in the Tac IPV at 6 months in 10 patients undergoing 3-weekly phone calls and regular follow-up calls (Tac SD −1.84; 95% CI: −2.95, −0.74; P = 0.004) compared with 7 controls undergoing only regular follow-up calls (Tac SD 0.59; 95% CI: −1.42, 2.60; P = 0.46) [ 73 ]. Telemedicine may be integrated with home-based dried blood spots (DBS) sampling of Tac for the purpose of therapeutic drug monitoring [ 74 , 75 ].…”
Section: General Interventions For Mna Prevention and Treatmentmentioning
confidence: 99%